Ensino-aprendizagem em serviço na educação para atenção farmacêutica - Simone de Araújo Medina Mendonça (2017)
This study aims to reveal the clinical competences developed by pharmacy undergraduate students in a pharmacy practice experiential program for pharmaceutical care practice (PPEP-PC). It is methodologically organized in five stages: I- identification of literature on experiential education in clinical pharmacy, with a systematic review in the databases Lilacs, PubMed, Scopus and Eric databases; II- development of a PPEP-PC applied to the Brazilian context; III- development of a practice setting for the provision of comprehensive medication management (CMM) services in the primary care setting to offer this experiential program in a professional pharmacy program of Minas Gerais, Brazil; IV- a quantitative descriptive study to evaluate the performance of PPEP-PC students in the identification and resolution of drug-therapy problems (DTP); V: an auto-ethnographic study on the development of clinical competences from the perspective of PPEC-PC participants, using participant observation, individual interviews, focus group and document analysis throughout PPEP-PC planning and implementation period (12 months). The systematic review revealed different organizational arrangements, pedagogical approaches and research used to evaluate experiential programs for education in pharmaceutical care. For the design of PPEP-PC, we adopted the experiential learning theory and the organizational arrangement that involved tutors and preceptors with students developing activities in public ambulatory clinics and, simultaneously, reflecting on their activities at the university. The practice setting was developed through a partnership between the university and the healthcare system that involved the delivery of CMM services to primary care patients . At the same time, PPEC-PC was implemented. Three graduate students took the role of tutoring seven professional students in the CMM service. One of the tutors was responsible for conducting the activities at the university. The quantitative study has shown that students were able to identify and propose resolutions for DTPs in a manner comparable to students and professionals in other studies. From the perspective of the participants, there was the development of competencies related to the philosophy of practice, to the Pharmacotherapy Workup (PW), to the management of the technical-scientific literature and to interprofessional relationships. It was noticed a gap in the previous training of students on pathophysiology, semiology and pharmacotherapy and on social sciences and humanities. These findings suggest that the PPEP-PC contributed to the development of clinical competences for pharmaceutical care in professional pharmacy students in the Brazilian educational and healthcare scenarios. In addition, the emerged knowledge about training gaps can contribute to the curriculum revision by the educational institution, and also redirect the learning process by students.